2017
DOI: 10.1080/02619768.2017.1315401
|View full text |Cite
|
Sign up to set email alerts
|

The challenges to discussing emotionally loaded stories in Finnish teacher education

Abstract: It has been increasingly acknowledged that emotions are a significant dimension in teachers' work and professional development, and an inseparable part of reflection promoted in the research-based teacher education. However, at the same time the difficulty of prompting student teachers to reflect on their emotions in teacher education has been recognised. This article focuses on this difficulty by examining how emotionally loaded stories about teachers' work were dealt with by soon-tograduate Finnish student t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…As a response to the observed need for bridging teacher education, induction support, and continuous in‐service professional development, 10,54,55 PGM has recently been also implemented in teacher education in order to combine teacher students and in‐service teachers in the same groups. In some cases, soon‐to‐graduate student teachers have participated in an optional PGM course lead by an experienced in‐service teacher, 28,56 whereas in some cases student teachers and in‐service teachers as mentees have formed mixed peer groups 28,29 . The results have been mainly positive and beneficial to both student teachers and teachers in working life.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a response to the observed need for bridging teacher education, induction support, and continuous in‐service professional development, 10,54,55 PGM has recently been also implemented in teacher education in order to combine teacher students and in‐service teachers in the same groups. In some cases, soon‐to‐graduate student teachers have participated in an optional PGM course lead by an experienced in‐service teacher, 28,56 whereas in some cases student teachers and in‐service teachers as mentees have formed mixed peer groups 28,29 . The results have been mainly positive and beneficial to both student teachers and teachers in working life.…”
Section: Resultsmentioning
confidence: 99%
“…While the study by Kaunisto et al 28 . showed that a facilitated peer group was an important forum for in‐service teachers to share their emotionally colored experiences, another study by Lassila et al 56 . showed that student teachers might find it difficult to reveal their vulnerability and deeper emotions and to respond constructively to peers’ emotional outpouring in a group.…”
Section: Resultsmentioning
confidence: 99%
“…Emotions have been increasingly recognized in studies on teachers ' work, self-understanding, commitment, well-being and exhaustion (e.g., Jokikokko et al, 2017;Lassila, Jokikokko, et al, 2017;Lassila, Timonen, et al, 2017). The topic of emotions is highly relevant in research on teacher socialization, given the fact that ECTs do not simply slide into an existing context but they also actively interpret and interact with the context (Kelchtermans & Ballet, 2002b).…”
Section: Emotions and Actions Through A Micropolitical Lensmentioning
confidence: 99%
“…Research concerning the role of the affective domain in teaching and in teacher education (e.g., [ 23 , 24 ]) revealed a significant gap between declarative knowledge and perceptions of the importance of educational themes—such as the affective domain—to the actual behavior or to behavior changes in this domain (e.g., [ 25 ]). When considering emotions as the mediators between knowledge and behavior [ 26 ], we found the affective domain to be a venue of research that can provide practical implications to teacher education programs and to teachers’ professional development programs.…”
Section: Introductionmentioning
confidence: 99%